Conceptions of value as family resemblances. Issue 4 (12th September 2016) - Fisher, Ron; Francis, Mark; Thomas, Andrew; Burgess, Kevin; Mutter, Katherine
Abstract : Purpose: The purpose of this paper is to consider value as individual and experiential, based on the relationships between conceptions of value, rather than attempting to identify a common factor. The authors use the term "family" to represent the relationships between conceptions of value and provide a philosophical basis that underpins this. The authors also propose an appropriate method for researching value as family resemblances. Design/methodology/approach: In this conceptual paper, the authors propose a new approach to understanding the nature of value in terms of family resemblances. In many marketing studies, value is described as being phenomenologically based, with an increasing number also emphasizing its experiential nature. Attempts to conceptualize value phenomenologically lead to tension between the search for an essence and the qualitatively different ways in which value is experienced by individuals. The authors propose phenomenography as a research approach that accommodates value based on differences rather than essences. Findings: Recognizing that there is no necessary condition or essence by which value may be defined resolves the tension that has arisen from the simultaneous search for a common feature and the assertion that value is experientially created by individuals. The research also highlights that the nature of value may differ between people, time and place or some aspects of it may be the same. Regarding value in terms of family resemblances accommodates actors' different conceptions of value. Phenomenography is an appropriate approach to operationalize conceptions of value in terms of family membership. Research limitations/implications: Understanding value as a family, and using phenomenography as method, provides methodological clarity to a long-standing research issue. Using the approaches outlined in this study will enable empirical studies of the nature of value in any context to be conducted soundly and relatively quickly. It will also provide a more inclusive and holistic set of values based on the experiences of individuals. Practical implications: The research provides important insights for practitioners through clearer conceptions of value. These include the ability to plan and deliver business outcomes that are more closely aligned with customer values. Understanding the conceptions of value experienced by actors in marketing, as determined through family resemblances, has clear implications for researchers and practitioners. Originality/value: Understanding actors' conceptions of value through the lens of family resemblances resolves a long-standing research issue. Using phenomenography as method is an approach seldom used in marketing that addresses the need for increased use of qualitative research in marketing.